Service FMECA of a bucket wheel excavator. (January 2020) - Pantelić, Milorad P.; Bošnjak, Srđan M.; Misita, Mirjana Z.; Gnjatović, Nebojša B.; Stefanović, Aleksandar Z.
Highlights: We presented a consistent approach to the quantification of risk for BWE. Results of experimental and numerical investigations are discussed. Corrective actions for reducing risk levels are provided. Abstract: Surface mining systems (SMSs) are among the most significant 20th century achievements in mining industry, whose significance to miners is comparable to the invention of dynamite in the 19th century. However, problems of SMS risk assessment are very scarce in relevant literature. For this reason, this paper aims to establish a consistent risk quantification approach for bucket wheel excavators (BWEs), the backbones of these systems. Based on the original structural scheme of a BWE, the risk parameters assessing criteria stemming from multidecadal experience and the database of recorded standstills (in the considered case, one hour of SMS downtime generates indirect financial losses of ≈15000€), a study was conducted applying the Service FMECA technique to the BWE SRs2000 (one of the best-selling models from "Takraf"), with the following conclusions: (a) the material conveying subsystem is the highest contributor in the total number of mechanical and electrical failures, as well as in total downtime; (b) during the monitoring period, there were no extreme risk level failures. Besides, corrective actions for reducing risk levels of the most critical mechanical and electrical failure modes are given in the paper. The presented approach for risk quantification for a BWE can be successfully applied to other SMS subsystems, notably spreaders.